Uma análise dos limites da firma: integração vertical e investimento externo direto em ambientes com rigidez ambiental - Azevedo Neto, Oly (Universidade do Vale do Rio dos Sinos, 2016)
The objective of this study is to identify the relationship between foreign direct investment, the vertical integration of the firm, environmental rigidity of the host country and moderation that environmental capacity can have on this variable of the companies listed in WIR annual report - World Investment Report, released by UNCTAD - United Nations Conference on Trade and Development in 2013. It used data analysis in cross section (cross section) from the collection of secondary data in UNCTAD's database, the world bank (Data World Bank), in management and sustainability reports and Netherland Organization for Applied Scientific Research and National Institute of Public Health's Environment Emission Database for Global Atmospheric Research 92 companies listed in the WIR report, which is published annually by UNCTAD, identifying the foreign direct investment suffer negative influence of vertical integration leading companies choose to market structures to invest and environmental capabilities are positively related to the dependent variable. They were identified in the sample analyzed relations between investment and environmental stiffness of the country nor the influence of moderation that environmental capacity could have on the stiffness.
Keywords: Investimento externo direto; Integração vertical; Rigidez ambiental; Capacidade ambiental; Capacidade ambiental; Foreign direct investment; Vertical integration; Stiffness environment; Environmental capacity; ACCNPQ::Ciências Sociais Aplicadas::Administração